Attachment Dimensions, Patterns Of Interaction During Conflict And Marital Satisfaction Among Married Individuals - Hasim, Marshina Juliza Mohd (2018)
This study aims to create a comprehensive model integrating adult romantic attachment dimensions, patterns of interaction during conflict and marital satisfaction. The application of Attachment Theory in this study was established via two dimensions of anxiety and avoidance. This study comprises two parts. Part One of the study examined the relationship between individual respondent’s childhood attachment dimensions with mother, father, peers and adult romantic attachment dimensions. Part Two of the study sought to determine if adult romantic attachment dimensions acted as a predictor to marital satisfaction through the mediating role of communication patterns during conflict. By means of survey method, data was collected using self-reporting questionnaire involving 400 married individuals in the state of Penang. Partial Least Squares (PLS) analysis was employed and result from the analysis yielded all the constructs have composite reliability value of more than 0.6 and convergent and discriminant validity with an average variance extracted (AVE) value greater than 0.50. The final model in Part One and Part Two recorded high Goodness of Fit (GoF) values at 0.681 and 0.401 respectively. The first model in Part One predicting on adult romantic attachment dimensions showed a strong explanatory power with R2 values of 73% in anxiety with spouse and 63.9% in avoidance with spouse. Additionally, the second model in Part Two indicated slightly lower explanatory power with R2 value of 39.5% on marital satisfaction. The results of Q2 tests proposed for both parts are well predicted by the model.